A study of the land productivity of Nueva Ecija and its implications for science teaching in the Central Luzon Polytechnic College - Barnachea, Cosme P. 1918- ([Quezon City s.n.], 1972)
This paper studied the land productivity of Nueva Ecija and its implications for science teaching in the Central Luzon Polytechnic College. It aimed primarily at finding some of the perplexing problems of land utilization so that when such problems are identified they may be remedied in order to attain maximized production. The solution of such problems can be made possible with full cooperation from the people, from the government officials, from the land users and from the young people especially the science students at the Central Luzon Polytechnic College. Public awareness to these problems is necessary so that they may be encouraged to direct their best effort and time toward the optimization of production.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Central Luzon -- Polytechnic College; Land -- Philippines -- Nueva Ecija; Agriculture -- Economic aspects -- Nueva Ecija